OP0194 Hexameric S100A12 is Required for Pro-Inflammatory TLR4-Signalling. (9th June 2015) - Kessel, C.; Fühner, S.; Brockmeyer, S.; Wittkowski, H.; Föll, D.
Abstract : Background: The human granulocyte-specific Ca 2+ -binding protein S100A12 is particularily over-expressed in autoinflammatory diseases such as juvenile idiopathic arthritis (JIA) as well as other inflammatory conditions (i.e. infections, vasculitides) and has been ascribed to the group of pro-inflammatory damage associated molecular pattern molecules (DAMPs) [1]. In order to operate as DAMP, S100A12 requires binding to cellular receptors. Although the protein was originally found to bind the receptor of advanced glycation endproducts (RAGE) [2], we recently demonstrated S100A12 to stimulate proinflammatory cytokine production in monocytes via TLR4 instead of RAGE [3]. Objectives: DAMP:TLR4 signalling is often discussed controversial. Mechanistic insights into the protein:receptor interaction as available for HMGB1, for example, can help to explain the powerful pro-inflammatory potential of these proteins. Upon Ca 2+ and Zn 2+ -binding S100A12 can oligomerize into di-, tetra- or hexamers [4]. In this study we assessed the mechanism of the S100A12:TLR4 interaction for these individual protein complexes. Methods: We performed extensive chemical crosslinking studies to assess S100A12 oligomerisation of both recombinant as well as native protein in autoinflammatory patients' sera as well as inside granulocytes. For receptor-interaction studies, defined LPS-free chemically crosslinked S100A12-complexes were isolated via combined HPLC and gel filtration. TLR4-binding and signalling was tested on receptor-expressing cell lines as well as primary human cells. Cytokine expression in response to stimulation was quantified on mRNA and protein level. Results: In our assays, only combined presence of Ca 2+ and Zn 2+ concentrations in extracellular ionic-strength could induce S100A12 hexamer-formation. Intracellular Ca 2+ /Zn 2+ -levels could only induce oligomerisation up to the tetrameric complex. Correspondingly, we could detect hexameric S100A12 in patients' serum, while we did not find this particular protein complex inside granulocytes. In vitro binding assays as well as cell stimulation experiments using chemically crosslinked HPLC-separated S100A12-oligomers revealed the S100A12-hexamer as the paramount TLR4-targeting pro-inflammatory active complex. Stimulation could be abrogated by interfering with TLR4-binding and, in particular, by blocking access to CD14. Conclusions: We have identified the S100A12-complex, which is responsible for pro-inflammatory signalling through TLR4. This is of great interest for designing improved diagnostics as well as precisely targeted therapeutic approaches, as currently tested with us. References: Kessel C, Holzinger D, & Foell D (2013) Phagocyte-derived S100 proteins in autoinflammation: putative role in pathogenesis and usefulness as biomarkers. Clin Immunol 147(3):229-241. Hofmann MA, et al. (1999) RAGE mediates a novel proinflammatory axis: a central cell surface receptor for S100/calgranulin polypeptides. Cell 97(7):889-901. Foell D, Wittkowski H, Kessel C, et al. (2013) Proinflammatory S100A12 can activate human monocytes via Toll-like receptor 4. Am J Respir Crit Care Med 187(12):1324-1334. Moroz OV, Blagova EV, Wilkinson AJ, Wilson KS, & Bronstein IB (2009) The crystal structures of human S100A12 in apo form and in complex with zinc: new insights into S100A12 oligomerisation. J Mol Biol 391(3):536-551. Disclosure of Interest: None declared